Model Pengembangan Kurikulum di MI Masalikil Huda 01 Tahunan Jepara - Ahmad Mawahibur Riski; Ainul Izzah Arrofiq; Kumala Hayati; Vina Rahmawati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
The importance of maintaining the relevance of education to the dynamics of current developments requires real efforts in curriculum development. Apart from that, the application of curriculum development models is key in the process of developing the curriculum. The use of a curriculum development model is necessary to systematically and purposefully design an educational plan. This research aims to determine the curriculum development model implemented at MI Masalikil Huda 01 Annually Jepara. The research method used is descriptive qualitative-case study. The subject of this research is MI Masalikil Huda 01 Tahunan Jepara with the source informant being Mrs. Rujiah, SE as the principal of MI Masalikil Huda 01 Tahunan Jepara. The selection of research subjects was carried out through purposive sampling and snowball sampling techniques. The data analysis technique in this research involves several steps, namely data collection accompanied by analysis during the collection process, data reduction, data segmentation to group the reduction results into smaller units, forming categorization, and drawing conclusions. The results of this research show that MI Masalikil Huda 01 Tahunan Jepara uses a combination curriculum development model between the administrative curriculum development model and the Grass Roots curriculum development model.